The Flora of Azulejos in Maranhão, Brazil - Leandro Menezes; Alícia Ewerton; Amanda Garcia; Susana Dominici; Fabiane Fernandes; Lívia Flávia Campos; Lucas Marinho (Ethnobiology Letters, 2021)
The azulejo (tile) styles from the Iberian Peninsula and other regions in the New World are strongly influenced by Muslim aesthetics. Many of the azulejos in Maranhão, Brazil, depict plants and plant parts, but little is known about their species identity. In this paper, we investigated the origin of 94 plants species illustrated on the azulejos in Maranhão based on their phytomorphic elements. Among them, twenty-five were from Asteraceae and eight were from Rosaceae. Most of the pieces are of Portuguese origin and the illustrations on the azulejos show a European lifestyle. For Brazilians, there was certainly no sense of belonging since the illustrations depict characteristics that are different from what is seen locally. Although the phytomorphic illustrations do not reflect local flora, azulejos have become the most characteristic symbol of Maranhão. Our research provides a preliminary data base upon which future works can be based to propose new prints of Maranhão plants and create digital guides that link historical information with botanical identifications.